Behavior of Piled Raft Foundation in Soft Clay Layer with Geo-Foam Application - Gultom, Juni; Pratikso, H; Rochim, Abdul; Taufik, Syahril (Budapest International Research and Critics University, 2021)
Piled raft system proves to be more effective on such problematic soft soil conditions. It takes the high vertical load and used to bring the settlement, differential settlement and tilting of structure within the permissible limit. Piled raft system proves to be cost effective than the conventional pile foundation system. Piled raft foundation accounts for complex soil-structure interaction, which needs interaction between structural engineer and geotechnical engineer. Geo-foam application is introduced below the footing to enhance floating resistance. The performance behavior of piled raft foundation in clayey soil and layered soil is carried out using laboratory experimental and then verified by 2D PLAXIS. There is a significant relationship between the decreases in settlement of the piled raft due to hydrostatic uplift.